Policing the Police: The Need for Law Enforcement Transparency - David Cuillier (The Journal of Civic Information, 2023)
More and more research indicates increased difficulty in the public acquiring information about mass shootings, police misconduct, prisons, and other law enforcement actions in the United States. This editor's note calls for more attention to studies that explore the state of law enforcement transparency, and methods for better informing the public.